PROBLEMS OF POLICY OF THE SOVIET STATE IN THE FIELD OF CULTURE IN THE UKRAINIAN VILLAGE IN 1930-TH IN RESEARCHES OF RESEARCH WORKERS OF UKRAINIAN DIASPORA AND FOREIGN AUTHORS - Мандрик, Я. І. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Idea, 2019)
In the article there have been analyzed the works of Ukrainian diaspora scientists and foreign authors devoted to the rural culture of Soviet Ukraine in 1930-tieth. On the basis of historical methods and objectivity the author has evaluated these research works and underlined their significance for the investigation of the important problem in the history of Ukraine.